The Effectiveness of the Semantic Map Strategy in Developing the Meta-Cognitive Thinking Skills of Secondary Stage Students in Social Studies in Kuwait - Alali, Abdullah Hamed (Journal of Curriculum and Teaching Methodology, 2022)
The current study aimed to find out the effectiveness of the Semantic map strategy in developing your skills in higher knowledge for Secondary school students in International social studies in Kuwait. It contains eleventh grade students in Saad bin Rabee Al-Ansari Secondary School for Boys, where the number of students reached (44) students. They were chosen intentionally, and they were divided into two groups; an experimental group, and a control group, and they were randomly allocated by 22 students for each group. The study depends on the semi-experimental approach. Therefore, to achieve the study objectives, the researcher improved the higher- knowledge consciousness skills and making sure of the psychometric properties before applying them. the results showed the presence of apparent differences between the performance of the two groups; the control and the experimental one; depending on the higher-knowledge consciousness skills standard. In view of the study results, the researcher came up with many recommendations; such as encouraging the social studies teachers, especially psychology teachers, to follow the semantic mapping strategy while teaching the material.